1991
DOI: 10.1002/app.1991.070430804
|View full text |Cite
|
Sign up to set email alerts
|

Plasma deposition modified nylon 4 membranes for hemodialysis

Abstract: SYNOPSISThe purpose of this research is to prepare high solute permeability membranes for hemodialysis by plasma depositing hydrophilic monomers onto chemically treated or O2 plasma etched Nylon 4 substrate. The factors that affect the performances of membranes, such as deposition conditions and chemical or plasma etching conditions, were studied. The monomers used in this study were 1-vinyl-2-pyrrolidone ( V P ) , 2-Hydroxyethyl methacrylate (HEMA), and Methyl methacrylate (MMA) . The permeabilities of NaCl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…1). This ratio compares well with the ratio (3.8) reported by Lai et al for 2-hydroxyethyl methacrylate deposited Nylon 4 substrate [47]. Tsai [48] also reported that heparin immobilization on tissue induced a decrease of fibrinogen adsorption and an increase of albumin adsorption.…”
Section: Protein Adsorptionsupporting
confidence: 78%
“…1). This ratio compares well with the ratio (3.8) reported by Lai et al for 2-hydroxyethyl methacrylate deposited Nylon 4 substrate [47]. Tsai [48] also reported that heparin immobilization on tissue induced a decrease of fibrinogen adsorption and an increase of albumin adsorption.…”
Section: Protein Adsorptionsupporting
confidence: 78%
“…Nylon 4 membranes have been regarded as promising membrane materials for separation purposes because of their excellent strength and inherent affinity to water. 60Co irradiation, chemical graft, and plasma deposition methods have been used to improve the performance of Nylon 4 for reverse osmosis (19), ultrafiltration (20), dialysis (21), and hemodialysis (22) as reported from our laboratory.…”
Section: Introductionmentioning
confidence: 97%
“…In addition min and fibrinogen, respectively, at 30ЊC for 1 h. The to the absorption peaks associated with pure SBS block measurement of the absorption of albumin and fibrincopolymer, the SBS-g-DMAEMA graft copolymer also ogen was performed following the process described had absorption peaks at 1700 cm Ϫ1 (CuO) and at about in the literature. 18 2760 cm Ϫ1 for the third amino group. Since the unreacted DMAEMA and its homopolymer were extracted Observation by SEM with hot methanol, the presence of this absorption The membrane was soaked in liquid nitrogen until it band confirms that the SBS-g-DMAEMA was a graft hardened.…”
Section: Measurement Of Absorption Of Albumin and Fibrinogenmentioning
confidence: 98%